Costs and productivity in automobile production : - Fuss, Melvyn A. (Cambridge University, 1992)
Motor vehicles are prominent among the flows of exports and/or imports for Canada, Germany, Japan, and the United States, and these trade flows are heavily influenced by the basic relative competitiveness of the production processes for automotive manufacturing. In this book the authors analyze the factors that contributed to the comparative cost competitiviness of the four countries' auto industries over the period 1961-1984 and disentangle the factors contributing to the Japanese cost and efficiency advantages. The authors provide estimates of comparative costs of automobile production (both short-run and long-run) and the sources of these cost differences, based on the econometric cost function methodology. An innovation is the careful treatment of capacity utilization, one of the most important sources of short-run cost and efficiency differences. This methodology is also used effectively in an analysis of the Canada-U.S. Auto Pact, a unique experiment in trade liberalization. Previous estimates of cost and efficiency differences using the plant inspection and comparison of company financial reports methodologies are also evaluated.